Javanese Worldview in The Social Media Commentary of Gus Baha’ - Fawaid, Ahmad; Aini, Intan Nur (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2024)
This article explores the Javanese worldview and the integration efforts of Gus Baha’s interpretations on social media. Despite numerous studies on Gus Baha’, there is a lack of research specifically linking the Javanese worldview with his Qur’anic interpretations. This study aims to examine how Gus Baha’s interpretations of the Qur’an influence the worldview of Javanese society, focusing on the responses and expressions of the audience towards his lectures. The research employs a qualitative method, using primary data from Gus Baha’s lecture videos on YouTube and audience comments, as well as secondary data from academic literature. Data collection includes observation, content analysis, and literature review. The analysis involves video transcription, thematic coding, and a hermeneutic approach to understand the interaction between interpretations and local Javanese traditions. The findings indicate that the Javanese worldview plays a significant role in the dissemination of localized interpretations, bridging Islamic insights with local traditions. Furthermore, this study underscores a trend in Indonesia from a literal interpretation model to an audiovisual one. The study highlights the need for further research on the relationship between religion and culture in the context of technology and recommends the development of policies to support digital dakwah.